If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
2*(5-((1/2)*y))-(7*y) = -6 // + 6
2*(5-((1/2)*y))-(7*y)+6 = 0
2*((-1/2)*y+5)-7*y+6 = 0
2*(5-1/2*y)-7*y+6 = 0
2*(5-1/2*y)-7*y+6 = 0
6-8*y+10 = 0
16-8*y = 0
16-8*y = 0
16-8*y = 0 // - 16
-8*y = -16 // : -8
y = -16/(-8)
y = 2
y = 2
| (2x-1)=(x+31) | | t^3-3t^2+2t+4=0 | | 5x^2+2xy+2y^2-12x-6y+9=0 | | 7.7+8.1x=x+16.8 | | 6=.3x+5 | | 6x-54/7x-63 | | x/600=4/3 | | x/600=16/9 | | 2/(15-3x) | | 2x+x=46 | | 4(m-1)=24 | | 2/15-3x | | y^2-1/3x | | 7(w-1)=28 | | (5u-7)/(4u-12) | | 2(n-2)=20 | | 15=5h+5 | | -2z-5=-17 | | -6f+4=40 | | -g=44 | | 9-x=3/5 | | -9p+3=21 | | -1.7(a+18)=-0.7(a+19) | | 0.7x=14x | | 4(x+3)+3x=3(x+4)+4x | | 9x^2+7x=-8 | | -d=75 | | 9/5-x=3 | | 9/5-x=4 | | 3y+1=2y+9 | | 6s=s+40 | | 25-x=87 |